Clinical trial simulation to evaluate population pharmacokinetics and food effect: Capturing abiraterone and nilotinib exposures. (4th February 2015) - Li, Claire H.; Sherer, Eric A.; Lewis, Lionel D.; Bies, Robert R.
Abstract The objectives of this study were to determine (1) the accuracy with which individual patient level exposure can be determined and (2) whether a known food effect can be identified in a trial simulation of a typical population pharmacokinetic trial. Clinical trial simulations were undertaken using NONMEM VII to assess a typical oncology pharmacokinetic trial design. Nine virtual trials for each compound were performed for combinations of different levels of between‐occasion variability, number of patients in the trial, and magnitude of a food covariate on oral clearance. Less than 5% and 20% bias and precision were obtained in individual clearance estimated for both abiraterone and nilotinib using this design. This design resulted in biased and imprecise population clearance estimates for abiraterone. The between‐occasion variability in most trials was captured with less than 30% of percent bias and precision. The food effect was detectable as a statistically significant covariate on oral clearance for abiraterone and nilotinib with percent bias and precision of the food covariate less than 20%. These results demonstrate that clinical trial simulation can be used to explore the ability of specific trial designs to evaluate the power to identify individual and population level exposures, covariate, and variability effects.